Implementasi Peraturan Mahkamah Agung Nomor 4 Tahun 2020 dalam Perkara Narkotika Pasca Pandemi (Studi Kasus di Pengadilan Negeri Kepanjen Kabupaten Malang) - Asma F; Supriyadi Supriyadi (Postgraduate University of Merdeka Malang, 2023)
Supreme Court Regulation No. 4 of 2020 aims to guarantee the right of the accused to obtain prompt legal certainty for the criminal offence alleged to him through trial without undue delay. After the Covid-19 pandemic, how did Perma's execution take place in Kepanjen State Court. The issues in this study include: how the implementation of the Supreme Court Regulation No. 4 of 2020 in the case of post-pandemic narcotic drugs covid-19 and whether the obstacles to the application of the Rules of the High Court No. The method used in this research is empirical jurisprudence, i.e. primary data or data obtained directly from the research site as well as secondary data that comes from legislative regulations and books. The results of the study revealed that the State Court for the Post-Covid-19 pandemic in conducting the trial is still being conducted online due to difficulties in presenting the accused. So the most effective thing to do is an online trial. There are rules on the legality of electronic proceedings through the Supreme Court Regulation No. 4 of 2020 on Administrative and Criminal Proceedings in Electronic Courts.